(untitled) (Journal of Tropical Resources and Sustainable Science (JTRSS), 2025)
The extent to which rice farmers are exposed to pesticides is significantly influenced by their handling practices and use of personal protective equipment (PPE). This study collected contextual information from 20 rice farmers affiliated with the Kemubu Agricultural Development Authority (KADA) in Pasir Mas, Kelantan. The farmers were surveyed between July 2024 and April 2025. Data were collected through personal interviews and questionnaire surveys, and analysed using descriptive statistical methods. The farmers were aged 21 to 87 years, had 4 to 50 years of experience, and cultivated paddy fields ranging in size from 0.8 to 12.1 hectares. All of the farmers applied pesticides using manual and/or motorised backpack sprayers, with twelve of them having received KADA training between 2022 and 2024. However, none of them reported using alternative pest management methods. The most commonly used pesticides were liquid formulations (4-12 products per farmer), with insecticides being the most frequently used (2-7 products per farmer). All farmers reported using at least one product classified as WHO classes II or III, and some used unregistered and expired products. The most common method of disposing of empty pesticide containers was burying them in the ground (13 farmers). While all farmers wore basic protective clothing (long sleeves and long pants), only 14 wore non-absorbent gloves and boots. These findings suggest gaps in safe pesticide handling practices and PPE use, indicating the need for targeted training and behavioural change interventions, as well as improved access to appropriate protective equipment and waste disposal facilities for the rice farmers in the region.